THE INFLUENCE OF COMPENSATION, COMPETENCY, FACILITIES AND INFRASTRUCTURE ON TEACHER PERFORMANCE AND WORK MOTIVATION AS AN INTERVENING VARIABLE IN PRIVATE SCHOOL - Amit Silitonga; Chabblullah Wibisono; Muhammad Gita Indrawan; Indrayani; Ngaliman (CV. Radja Publika, 2023)
This research aims to analyze the influence of compensation, competency and infrastructure on teacher performance at Yos Anugrah and Sinar Timur Atam private schools with motivation as an intermediary variable. The methods used in this research are quantitative and qualitative research methods and also mixed research methods. The total population were 178 teachers. Data collection techniques used questionnaires. The data obtained were analyzed by using the SEM AMOS analysis techniques. The results of this studies show that compensation has a slight direct effect on work motivation, showing a probability value of 0.157 (p>0.05), competence has a slight direct effect on work motivation showing a probability value of 0.254 (p>0.05) and infrastructure has a direct effect on work motivation obtained at 0.038, testing the relationship between these two variables shows a probability value of 0.038 (p<0.05).